The First Report of the Occurrence of the Root Mealybug Ripersiella multiporifera Jansen (2008) (Hemiptera: Coccoidea: Rhizoecidae) in Indonesia - Devi, Komang Saraswati; Sudiarta, I Putu; Sunari, Anak Agung Ayu Agung Sri; Wirya, Gusti Ngurah Alit Susanta; Devi, Putu Shinta; Eka Wijayanti, Febri (Journal of Tropical Biodiversity and Biotechnology, 2024)
Ripersiella multiporifera is a root mealybug species within the family Rhizoecidae that has distinctive bitubular pores on the dorsal and ventral. This species was first discovered by Jansen (2008) in the Netherlands during an import interception of Sansevieria sp. from Indonesia and Hoya kerrii from Thailand. This species was also found during inspections in Sicily (Italy) on the roots of Sansevieria trifasciata. In Indonesia, there are no reports of the existence of R. multiporifera, emphasising the need for research on its presence. This work was conducted the morphological method based on modified determination key and the molecular method based on MtCOI gene. The identified species was R. multiporifera, and this finding represents the first evidence of R. multiporifera's presence in Bali (Indonesia) which can be used as a reference for future research, especially in population control approaches.